Comprehensive whole-genome resequencing unveils genetic diversity and selective signatures of the Xiangdong black goat - Liu, Ziao; Li, Haobang; Luo, Yang; Li, Jianbo; Sun, Ao; Ahmed, Zulfiqar; Zhang, Baizhong; Lei, Chuzhao; Yi, Kangle (Frontiers in Genetics, 2024)
Xiangdong black goats, indigenous to Hunan Province, China, exhibit remarkable adaptation to challenging environments and possess distinct black coat coloration alongside exceptional meat quality attributes. Despite their significance, comprehensive genomic investigations of this breed have been notably lacking. This study involved a comprehensive examination of population structure, genomic diversity, and regions of selection in Xiangdong black goats utilizing whole-genome sequencing data from 20 samples of this breed and 139 published samples from six other Chinese goat breeds. Our genomic analysis revealed a total of 19,133,125 biallelic single nucleotide polymorphisms (SNPs) within the Xiangdong black goat genome, primarily located in intergenic and intronic regions. Population structure analysis indicated that, compared with Jintang, Guizhou and Chengdu goats, Xiangdong black goats exhibit a reduced level of genetic differentiation but exhibit relatively greater divergence from Jining goats. An examination of genetic diversity within Xiangdong black goats revealed a moderate level of diversity, minimal,